Effect of Modified Atmosphere Packaging on Qualities and Shelf Life of Precooked Baby Clam (Paphia undulata) - Punchira Vongsawasdi; Montira Nopharatana; Juthamas Khueankhancharoen; Chonisa Changyoug (Agriculture and Natural Resources, 2011)
The effect of modified atmosphere (20% CO2 + 20% O2 + 60% N2, 40% CO2 + 20% O2 + 40% N2, 60% CO2 + 20% O2 + 20% N2) on the quality and shelf life of precooked baby clams was investigated. Baby clams were blanched in boiling water until the temperature in the center of meat reached 73 ± 2 °C for 1 min. The precooked samples were packed in nylon laminated with polyethylene (Nylon/PE) bags and kept at 4 ± 2 °C. The results indicated that as the storage time increased, the total plate count, % drip loss, total volatile base nitrogen (TVB-N), trimethylamine (TMA) and pH of the precooked products, regardless of the atmospheric conditions, increased while their firmness and sensory scores decreased. All products, regardless of the modified atmosphere packaging conditions, showed better qualities and had longer shelf life compared with those packed under atmospheric conditions. Precooked clam meat in 20% CO2 + 20% O2 + 60% N2, 40% CO2 + 20% O2 + 40% N2 and 60% CO2 + 20% O2 + 20% N2 packages could be kept at 4 ± 2 °C for 15, 21 and 24 d, respectively whereas the products packed under atmospheric conditions had a shelf life of 10 d. The results revealed that 60% CO2 + 20% O2 + 20% N2 was the most effective storage condition for refrigerated precooked baby clam. The product was orange-yellow in color, elastic and slightly stiff with no exotic flavor, and was liked moderately by the panelists.